Comparison of family environmental scale (FES) subscales between Malaysian setting with the original dimension of FES - Bujang, Adam; Musa, Ramli; Haniff, Jamaiyah; Muhammad, Noor Azimah; Omar, Khairani (Malaysian Journal of Psychiatry, 2010)
Introduction: Family Environment Scale (FES) was developed by Moos1, has ten subscales and was categorized into three dimensions. Objective: The objective of this study was to develop factor structure for the Malay-translated version of the FES subscales. Methodology: The study used Malay translated version of FES by Khairani et. al2. This study was a multi centre, cross-sectional study, involving four secondary schools consisted of adolescents, aged between 12-17 years old and a total of 295 participants were enrolled in this study. Exploratory factor analyses was done across two groups of analysis set on the subscales with Cronbach’s alpha more than 0.50 and 0.53 respectively. Results: Two distinct factors were extracted across the four subscales consisted of Cohesion, Conflict and Organization in factor 1 and only Control in factor 2. Conclusion: The finding indicated that element of Cohesion, Conflict and Organization has a good indicator of a good family relationship.